2018
DOI: 10.1177/1933719117718276
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of GdA Expression in Endometrium of Women With Endometriosis: Implication for Endometrial Receptivity

Abstract: Glycodelin-A (GdA) has been proposed to represent a potential biomarker of endometrial function, but little is known about its expression during the different phases of the menstrual cycle and under pathological conditions. In the light of its potential importance also in embryo implantation, we aimed to evaluate the expression profile of GdA as well as the presence of different glycosylated glycoforms and the immunolocalization in endometrial tissue from women with endometriosis and in women with proven ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
2
27
0
1
Order By: Relevance
“…In particular, five spots could be detected in ORG-pp, corresponding to five known glycoforms of GdA, with the less acidic spot (spot number 1) being scarcely evident ( Figure 5B); instead, in ORG-msp, 6 glycoforms are expressed; among them four glycoforms were prominent, while the forms 1 and 6 (spotted only in this model) were barely identifiable ( Figure 5C). Therefore, as summarized in Figure 5D, comparative evaluation of total GdA expression levels, as well as of its gluco-isoforms, in organoids after hormonal treatments is in full agreement with our previously reported data in whole endometrial tissues [26], indicating a peak in GdA expression at the implantation window corresponding to a mid-secretory phase. The appearance of a specific isoform, absent in the proliferative phase model is the additional feature observed in a 2D or 3D model.…”
Section: Human Endometrial Organoids Recapitulate the Glycodelin (Gdasupporting
confidence: 91%
See 3 more Smart Citations
“…In particular, five spots could be detected in ORG-pp, corresponding to five known glycoforms of GdA, with the less acidic spot (spot number 1) being scarcely evident ( Figure 5B); instead, in ORG-msp, 6 glycoforms are expressed; among them four glycoforms were prominent, while the forms 1 and 6 (spotted only in this model) were barely identifiable ( Figure 5C). Therefore, as summarized in Figure 5D, comparative evaluation of total GdA expression levels, as well as of its gluco-isoforms, in organoids after hormonal treatments is in full agreement with our previously reported data in whole endometrial tissues [26], indicating a peak in GdA expression at the implantation window corresponding to a mid-secretory phase. The appearance of a specific isoform, absent in the proliferative phase model is the additional feature observed in a 2D or 3D model.…”
Section: Human Endometrial Organoids Recapitulate the Glycodelin (Gdasupporting
confidence: 91%
“…This selective expression suggests a crucial role in the endometrial receptivity of this glycoform of GdA that has been already suggested to act as a key regulatory protein during the embryo attachment to the recipient endometrial epithelium [23]. Interestingly, endometrial expression of GdA, as well as its glycoforms composition significantly change during the menstrual cycle in women affected by endometriosis [26]. This hormone-dependent condition that affects up to 5-10% of women in their reproductive age, is characterized by the abnormal growth of endometrial tissue in ectopic sites, outside the endometrial cavity, as well as by a significant reduction in fertility [27].…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The expression of integrin αvβ3 in endometriosis is impaired, while HOXA10, a transcription factor that stimulates αvβ3 expression is reported to be decreased, with its methylation also being modified ( 45 ). The expression of other transplantation factors is also affected in endometriosis, including glycodelin A ( 46 ), osteopontin ( 47 ), leukemia inhibitory factor ( 48 ) and lysophosphatidic receptors 2 and 4 ( 49 ).…”
Section: Endometriosis-associated Infertilitymentioning
confidence: 99%